2021
DOI: 10.3389/fimmu.2021.717688
|View full text |Cite
|
Sign up to set email alerts
|

PTP4A3 Is a Prognostic Biomarker Correlated With Immune Infiltrates in Papillary Renal Cell Carcinoma

Abstract: PTP4A3 plays an important role in the tumorigenesis and metastasis of multiple tumors, but its prognostic role in renal cancer is not well understood. We utilized the Oncomine and Tumor Immunoassay Resource databases to examine the differential expression of PTP4A3 in tumor tissues and normal tissues in breast, urinary tract, gastrointestinal tract and skin. Using the GEPIA and PrognoScan databases, the independent prognostic role of PTP4A3 was confirmed in clear cell renal cell cancer and papillary renal cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Furthermore, the inhibitory efficiency of mAb 12G12 was negatively correlated with PRL-3 expression in lung cancer (lower expression of PRL-3 in PG, higher suppression of cell migration) and pancreatic cancer (higher expression of PRL-3 in ASPC-1, lower suppression of cell migration) ( Supplementary Figure 2 B-2G). Our previous study and other group's reports indicated that the prospect of PRL-3 research may hide in the tumor microenvironment, including secreting factors, exosomes, and immune cells 15 , 25 , 27 . Therefore, we believe that mAb 12G12 may be applied in the treatment of solid tumors through different mechanisms.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, the inhibitory efficiency of mAb 12G12 was negatively correlated with PRL-3 expression in lung cancer (lower expression of PRL-3 in PG, higher suppression of cell migration) and pancreatic cancer (higher expression of PRL-3 in ASPC-1, lower suppression of cell migration) ( Supplementary Figure 2 B-2G). Our previous study and other group's reports indicated that the prospect of PRL-3 research may hide in the tumor microenvironment, including secreting factors, exosomes, and immune cells 15 , 25 , 27 . Therefore, we believe that mAb 12G12 may be applied in the treatment of solid tumors through different mechanisms.…”
Section: Discussionmentioning
confidence: 87%
“…Overexpression of SPON2 has been shown to promote tumor cell migration by promoting M1/M2-like Macrophage recruitment in colorectal cancer and liver cancer ( Zhang et al, 2018 ; Huang et al, 2021 ). PTP4A3 was also consider as a prognostic biomarker correlated with immune infiltrates in papillary renal cell carcinoma ( Song et al, 2021 ). In summary, we speculated that high expressed TRPV2 would result to the development of UVM by regulating immune response.…”
Section: Resultsmentioning
confidence: 99%
“…In most cases, the human PRL-3 gene has a solitary copy on chromosome 8, near the long arm, with 9613 nucleotides in length. Increased levels of PRL-3 have been documented in cases of liver cancer, breast cancer, ovarian cancer, papillary renal cell carcinoma, and various other conditions [ 40 , 41 , 42 , 43 ]. This elevation could potentially impact the disease’s prognosis.…”
Section: Regulatory Mechanisms Of Prl-3mentioning
confidence: 99%